CIVIL FORUMS N CENTRAL ASIA: GOALS, SPECIFICS, POTENTIAL - ERGASHEV, Bakhodyr (CENTRAL ASIA AND THE CAUCASUS, 2004)
In Central Asia, society is divided into three segments: the power vertical, business structures, and nongovernmental organizations (NGOs), which largely interact in keeping with time-tested international practices. What is more, the historical-cultural and national-religious characteristics of the region’s countries are modifying the structure of civil society in ways that are turning the nation-wide consolidation processes into something of a mindbender for researchers. This, together with the growing geopolitical role of the Central Asian countries, is giving research of the evolution of democratic institutions in these republics' vital scientific significance.